Influence of environmental factors in the adherence of an atypical enteropathogenic Escherichia coli strain to epithelial cells - Romao, Fabiano T.; Hernandes, Rodrigo T. [UNESP]; Yamamoto, Denise; Osugui, Lika; Popi, Ana Flavia; Gomes, Tania A. T. (Biomed Central Ltd, 2014)
Background: Attachment is essential to maintain bacteria at their preferential intestinal colonization sites. There is little information on the influence of different environmental conditions in the interaction of atypical enteropathogenic Escherichia coli (aEPEC) strains with epithelial cells. In this study, we evaluated the effect of different glucose (5 and 25 mM) and CO2 (0.03 and 5%) concentrations and presence of bile salts on the adhesiveness of the aEPEC strain 1551-2.Results: We found that a CO2-enriched atmosphere enhanced the adhesiveness of the aEPEC 1551-2 strain independently of glucose concentrations or presence of bile salts. Conversely, the presence of high glucose concentration altered the original localized adherence (LA) pattern observed at 5 mM glucose, which is characterized by the formation of compact bacterial clusters, to a hybrid adherence pattern (LA and an aggregative adherence-like pattern). In addition, at high glucose concentration, there was increased expression of the fimA gene, which encodes the major subunit of type 1 pilus (T1P), and an isogenic fimA mutant displayed only LA. The presence of bile salts did not interfere with the adhesion properties of the 1551-2 strain to HeLa cells.Conclusions: Our data suggest that a CO2-enriched atmosphere could favor aEPEC adhesion to the host cells, whereas enhanced T1P production under high glucose concentration could allow bacteria to access more extensive intestinal colonization sites in the host at the beginning of the infectious process.
Keywords: Atypical EPEC; Glucose; Type I pilus; Adherence; Environmental factors; Diarrhea